Carbon dioxide valorization into resveratrol via lithoautotrophic fermentation using engineered Cupriavidus necator H16 - Jang, Yongjae; Lee, Yeon Ji; Gong, Gyeongtaek; Lee, Sun-Mi; Um, Youngsoon; Kim, Kyoung Heon; Ko, Ja Kyong (BioMed Central, 2024)
Background Industrial biomanufacturing of value-added products using CO2 as a carbon source is considered more sustainable, cost-effective and resource-efficient than using common carbohydrate feedstocks. Cupriavidus necator H16 is a representative H-2-oxidizing lithoautotrophic bacterium that can be utilized to valorize CO2 into valuable chemicals and has recently gained much attention as a promising platform host for versatile C1-based biomanufacturing. Since this microbial platform is genetically tractable and has a high-flux carbon storage pathway, it has been engineered to produce a variety of valuable compounds from renewable carbon sources. In this study, the bacterium was engineered to produce resveratrol autotrophically using an artificial phenylpropanoid pathway. Results The heterologous genes involved in the resveratrol biosynthetic pathway-tyrosine ammonia lyase (TAL), 4-coumaroyl CoA ligase (4CL), and stilbene synthase (STS) -were implemented in C. necator H16. The overexpression of acetyl-CoA carboxylase (ACC), disruption of the PHB synthetic pathway, and an increase in the copy number of STS genes enhanced resveratrol production. In particular, the increased copies of VvSTS derived from Vitis vinifera resulted a 2-fold improvement in resveratrol synthesis from fructose. The final engineered CR-5 strain produced 1.9 mg/L of resveratrol from CO2 and tyrosine via lithoautotrophic fermentation. Conclusions To the best of our knowledge, this study is the first to describe the valorization of CO2 into polyphenolic compounds by engineering a phenylpropanoid pathway using the lithoautotrophic bacterium C. necator H16, demonstrating the potential of this strain a platform for sustainable chemical production.